Hypervascular Spinal Tumors: Influence of the Embolization Technique on Perioperative Hemorrhage - Berkefeld, Joachim; Scale, Detlef; Kirchner, Johannes; Heinrich, Thomas; Kollath, Jürgen (American Journal of Neuroradiology, 1999)
BACKGROUND AND PURPOSE: Corporectomy is an effective treatment for vertebral metastases; however, massive perioperative hemorrhage is often associated with this procedure. We compared preoperative particle, particle-coil, and coil embolizations of hypervascular spinal tumors prior to vertebral body replacement to determine which prevented perioperative hemorrhage most effectively.METHODS: The vertebral tumors of 59 patients were embolized prior to corporectomy. In 26 cases, only coils were used for the proximal occlusion of feeding segmental arteries. Twenty-four patients received a combination of polyvinyl alcohol (PVA) particles and coils, and nine tumors were embolized with particles alone. We compared intraoperative blood loss between the three groups and 10 other patients who did not undergo embolization prior to corporectomy.RESULTS: Estimation of intraoperative hemorrhage showed a median value of 4350 mL in patients without embolization, 2650 mL in cases of coil embolization, 1850 mL in cases of particle-coil embolization, and 1800 mL in cases of particle embolization. The difference between unembolized patients and those who underwent coil embolization was not statistically significant. Particle and particle-coil embolizations showed very similar results, and reduced hemorrhage significantly as compared to unembolized and proximal coil occlusion cases. Residual bleeding came from the venous system and the neighborhood of the embolized region.CONCLUSION: Particle embolization prior to corporectomy can reduce perioperative hemorrhage. The additional benefit of proximal coil occlusion of arterial feeders is questionable.